PENGARUH JENIS KELAMIN, IPK, PENGALAMAN KERJA TERHADAP LITERASI KEUANGAN (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU KEPULAUAN) - Cahyo Budi Santoso; Nur Habibah Pasaribu; Ade Isyana Hairunnisah (MEASUREMENT : Jurnal Program Studi Akuntansi, 2022)
Impact of Gender, GPA, Work Experience on FinanciaThis concentrate on means to decide the impact of orientation, GPA, work insight on monetary proficiency of understudies of the Faculty of Economics and Business, University of Riau Islands. By utilizing the Slovin equation the example utilized was 89 respondents. Information was acquired by gathering information through a survey. Inspecting involving arbitrary examining and information investigation in this study is a different straight relapse model which is handled through SPSS programming. Education (Case Study of Students of the Faculty of Economics and Business, University of Riau Islands). Degree program. Accounting Study Program. Economy. Riau Archipelago University. The consequences of the investigation show that somewhat orientation, GPA, work experience significantly affect monetary proficiency. All the while orientation, GPA, work experience significantly affect monetary proficiency of understudies of the Faculty of Economics and Business, University of Riau Islands.